Activists, Non-activists, and Allies: Civic Engagement and Student Types at MSIs - Fassett, Kyle T.; Priddie, Christen; BrckaLorenz, Allison; Kinzie, Jillian (Frontiers in Education, 2018)
Higher education institutions across the country aim to contribute to students' ability to become active citizens. Civic engagement has long been an emphasis of higher education and has become a focal point from innovations such as the Carnegie Foundation's elective classification for community engagement and service-learning (Saltmarsh and Zlotkowski, 2011). Researchers have demonstrated that foundational values of democratic engagement including inclusiveness, relationships between students who engaged in cross-racial interactions, co-curricular activities and diversity experiences are related to higher levels of civic awareness and engagement (Bowman, 2011; Hurtado and DeAngelo, 2012). Furthermore, students who participated in protests were more likely to have complex thinking about democracy and awareness of global problems. Civic engagement is embedded in the history of minority student groups on college campuses, with their influence on increased access and resources, as well as their fight for more inclusive and productive campus environments (Abrego, 2008; Gasman et al., 2015; Borjian, 2018). Although civic engagement has been examined across various student groups, there is limited research on the impact of civic engagement at minority-serving institutions. This study uses a large-scale, cross-sectional approach to analyze college students' participation in civic engagement activities at 24 minority-serving institutions from 2013 to 2017 using data from the National Survey of Student Engagement (NSSE). Aspects of civic engagement examined include students' participation in events that address social or political issues, frequency of interactions with diverse others, participation in leadership and service-learning activities, and perceptions of their institution's contribution to their growth in areas such as becoming an informed and active citizen. Additionally, researchers explored students' ability to resolve conflicts that involve bias and prejudice and contribute to the well-being of their community; how frequently students inform themselves of state, national, or global issues; and how they may organize others around a common cause. The data led to the creation of three types of student activists. The results have implications for student affairs professionals, administrators, and faculty to redefine how students participate in civic engagement activities, to shape civic education experiences on their campus, and to help students learn how to find and use their voices.